Naturally occurring melanomas in dogs as models for non‐UV pathways of human melanomas. (1st November 2013) - Gillard, Marc; Cadieu, Edouard; De Brito, Clotilde; Abadie, Jérôme; Vergier, Béatrice; Devauchelle, Patrick; Degorce, Frédérique; Dréano, Stephane; Primot, Aline; Dorso, Laetitia; Lagadic, Marie; Galibert, Francis; et al.
Summary Spontaneously occurring melanomas are frequent in dogs. They appear at the same localizations as in humans, i.e. skin, mucosal sites, nail matrix and eyes. They display variable behaviors: tumors at oral localizations are more frequent and aggressive than at other anatomical sites. Interestingly, dog melanomas are associated with strong breed predispositions and overrepresentation of black‐coated dogs. Epidemiological analysis of 2350 affected dogs showed that poodles are at high risk of developing oral melanoma, while schnauzers or Beauce shepherds mostly developped cutaneous melanoma. Clinical and histopathological analyses were performed on a cohort of 153 cases with a 4‐yr follow‐up. Histopathological characterization showed that most canine tumors are intradermal and homologous to human rare morphological melanomas types – 'nevocytoid type' and 'animal type'‐. Tumor cDNA sequencing data, obtained from 95 dogs for six genes, relevant to human melanoma classification, detected somatic mutations in oral melanoma, in NRAS and PTEN genes, at human hotspot sites, but not in BRAF. Altogether, these findings support the relevance of the dog model for comparative oncology of melanomas, especially for the elucidation of non‐UV induced pathways.